Stadtentwicklung und Strukturwandel in Oberhausen. Ein Projekt des Stadtarchivs Oberhausen zur Erschließung, Forschung und Ausstellung. - Dellwig, Magnus (Deutsches Institut für Urbanistik, 2020)
The industrial city of Oberhausen in the Ruhr area in Germany is a settlement without any roots of social organization dating from the pre-industrial period. Oberhausen City Archives initiated a research project in cooperation with scientific institutions and will host an exhibition - "Aufbruch macht Geschichte" - that will showcase the long way of economic changes from an agrarian society to a service(-based) economy. One focus is on the period from 1896-1934. Oberhausen ushered in a new epoch of urban development, aiming to become a service-oriented city while also being a driving force for private investors.
Keywords: Stadtgeschichte; Stadtentwicklung; Strukturwandel; Industrialisierung; Tertiärisierung; Ausstellungskonzept; Stadtarchiv